2014
DOI: 10.1002/hep.26993
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocyte senescence by way of N-ras activation is a characteristic of primary sclerosing cholangitis

Abstract: Primary sclerosing cholangitis (PSC) is an incurable cholangiopathy of unknown etiopathogenesis. Here we tested the hypothesis that cholangiocyte senescence is a pathophysiologically important phenotype in PSC. We assessed markers of cellular senescence and senescence-associated secretory phenotype (SASP) in livers of patients with PSC, primary biliary cirrhosis, hepatitis C, and in normals by fluorescent in situ hybridization (FISH) and immunofluorescence microscopy (IFM). We tested whether endogenous and exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
256
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 210 publications
(271 citation statements)
references
References 49 publications
(126 reference statements)
15
256
0
Order By: Relevance
“…For example, we have shown that CCL2 and CX3CL1, which are components of the SASPs of senescent cholangiocytes, induced cellular senescence in cholangiocytes [45,49,65]. This effect may lead to the accumulation of senescent cholangiocytes in the affected ducts and also senescent mesenchymal cells around the bile ducts in fibrosing cholangiopathies.…”
Section: Bystander Effectmentioning
confidence: 95%
See 4 more Smart Citations
“…For example, we have shown that CCL2 and CX3CL1, which are components of the SASPs of senescent cholangiocytes, induced cellular senescence in cholangiocytes [45,49,65]. This effect may lead to the accumulation of senescent cholangiocytes in the affected ducts and also senescent mesenchymal cells around the bile ducts in fibrosing cholangiopathies.…”
Section: Bystander Effectmentioning
confidence: 95%
“…Collectively, the resultant periductal cytokine networks that are formed, contribute to biliary mucosal defense, and also the pathogenesis of fibrous cholangiopathy, and the subsequent acquired immunity [5,22,77,78,84,85]. A signaling pathway initiated by TLRs also involves activation of Ras, mediating the production of proinflammatory cytokines and chemokines by cholangiocytes such as IL6 followed by cholangiocyte proliferation [90], and also inducing cellular senescence, as described below [49]. These aspects of biliary innate immunity are shown in Fig.…”
Section: Senescence and Phenotypic Dedifferentiation Of Cholangiocytesmentioning
confidence: 98%
See 3 more Smart Citations